The tadpole of Hylodes babax Heyer, 1982 (Amphibia, Anura, Hylodidae) - Pirani, Renata Magalhães; Pezzuti, Tiago Leite; Motta, Ana Paula; Feio, Renato Neves (Zootaxa, 2011)
Frog species from the genus Hylodes Fitzinger occur mainly in southeastern Brazil (Frost, 2010).  Of the 24 species of genus only 13 species have their tadpoles described (see Discussion below). Hylodes babax was known from the type-locality at Caparaó mountain range (Heyer, 1982), and has recently been recorded from two new localities: Parque Estadual da Serra do Brigadeiro, in the Mantiqueira mountain range, and Floresta Estadual do Uaimií, in the southern Espinhaço mountain range (Pirani et al. 2010).